Book review of Leonardo Veliz (Ed., 2025). Multiculturalism and multilingualism in education. Brill. (Journal of Applied Learning and Teaching, 2025)
On 3rd March 2025, U.S. President Donald Trump signed a historic executive order designating English as the official language of the United States. Remarkably, this decision marks the first instance of a federally mandated official language since the nation’s founding nearly 250 years ago (Davies, 2025). This political act does not merely symbolise linguistic unification; rather, it exemplifies a broader global resurgence of monocultural and monolingual ideologies, at times escalating into overt hostility towards multilingual and multicultural identities. Indeed, across multiple nations, recent years have witnessed a troubling surge of what might be described as ‘anti-languages madness’ (Lo Bianco, 2025), where nationalist discourses promote exclusionary practices and linguistic intolerance.Against this troubling global backdrop, we are facing a paradox: while globalisation connects diverse cultures more closely than ever, many nations simultaneously retreat into isolationism. Pluralism, a concept thoughtfully explained by Banks and Banks (2020), is essential; it describes how various cultural identities can co-exist equitably in a shared society. Yet, the deep-seated monolingual mindset remains a stubborn barrier, and superficial diversity initiatives simply are not enough. To make meaningful societal progress, genuine pluralistic approaches are urgently needed (Veliz, 2025).Education lies at the very heart of this transformative journey. Classrooms around the world are becoming increasingly multicultural and multilingual, challenging traditional educational frameworks. Educators today across all subjects require new tools, training, and perspectives to effectively teach diverse student populations (Tao & Liyanage, 2020). This makes the volume Multiculturalism and Multilingualism in Education (published by Brill in 2025; see Figure 1), edited by Associate Professor Leonardo Veliz who currently serves as Head of Department – Curriculum at the University of New England, particularly timely and prominent.